2010
DOI: 10.1002/ajmg.a.33405
|View full text |Cite
|
Sign up to set email alerts
|

Kabuki syndrome and cancer in two patients

Abstract: Both hepatoblastoma and neuroblastoma are occasionally associated with congenital syndromes such as Beckwith-Wiedemann syndrome and trisomy 18. There have been no reports of hepatoblastoma in patients with Kabuki syndrome, whereas one patient with neuroblastoma and this syndrome has been reported. In this paper we present two patients with Kabuki syndrome and a neoplasm: a child of 6 years with hepatoblastoma and an infant, of 6 months affected by neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Until now, 6 Kabuki patients have been described that developed different types of cancer including pre-B-ALL, 70 hepatoblastoma, 71 neuroblastoma, 71 , 72 Burkitt lymphoma, 73 and fibromyxoid sarcoma 74 marking the Kabuki syndrome as a cancer predisposition syndrome.…”
Section: Constitutional Utx Defects Cause the Kabuki Syndromementioning
confidence: 99%
“…Until now, 6 Kabuki patients have been described that developed different types of cancer including pre-B-ALL, 70 hepatoblastoma, 71 neuroblastoma, 71 , 72 Burkitt lymphoma, 73 and fibromyxoid sarcoma 74 marking the Kabuki syndrome as a cancer predisposition syndrome.…”
Section: Constitutional Utx Defects Cause the Kabuki Syndromementioning
confidence: 99%
“…A single study showed that approximately 10% of children with HB carry germline mutations of APC (Aretz et al, ). HB also occurs in patients with Beckwith–Wiedemann syndrome (Mussa et al, ) and Simpson–Golabi–Behmel syndrome (Kosaki et al, ), and has been described in a few patients with Sotos syndrome (Kato et al, ), Kabuki syndrome ( KMT2D ; coding for histone methyltransferase; MIM 147920) (Tumino et al, ), Li–Fraumeni syndrome (Nichols, Malkin, Garber, & Li, ; Yoshida et al, ), and neurofibromatosis 1 (Ucar, Caliskan, Toy, & Gunel, ). Hepatoblastoma has also been rarely described in RASopathies, for example, Noonan syndrome (Yoshida, Ogata, Masawa, & Nagai, ) and cardiofaciocutaneous (CFC) syndrome ( BRAF ; MIM 115150) (Al‐Rahawan et al, ).…”
Section: Typical Childhood Cancer Types and Relevant Cpsmentioning
confidence: 99%
“…Patients 1 and 2 (Table 1) have been reported previously: the first for chemoembolization prior to surgery and the second due to the presence of Kabuki syndrome [13,14]. Neoadjuvant chemotherapy for hepatoblastoma and hepatocarcinoma patients, according to SIOPEL protocols, consisted in 4-10 courses (median, 4.5) of different combinations of cisplatin, doxorubicin, and carboplatin.…”
Section: Preoperative Managementmentioning
confidence: 99%